Program Evaluation on Qafilah Dakwah Zulhijah: A Review of Evaluation Studies Using CIPP Model Approach - Slamet Riyadi; Arifdo Putra; Salsa Ikhlasiyah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
This study aims to fully and thoroughly evaluate the Qafilah Da'wah Zulhijah STAI As-sunnah program using the CIPP framework (Context, Input, Process, Product). So, with this evaluation, STAI As-Sunnah can make a better future implementation decision. It can also be considered as material for discussion for other universities in Indonesia that have the same vision as STAI As-Sunnah. This research was carried out using a qualitative approach as a framework. Moreover, the concept of the CIPP evaluation is a reference in evaluating the Qafilah Da'wah Zulhijah STAI As-sunnah program. Data were collected using several qualitatively typical instruments: observation, interviews, and documentation. Then the data is strengthened using data and source triangulation techniques. Furthermore, the data were analyzed in depth and described objectively. In the Context Evaluation, it was found that the activities of the Da'wah Zulhijah Qafilah had a strong foundation. The Input Evaluation is also quite good, although some things need to be improved. In Process Evaluation, as a whole, went well. Likewise, with Product Evaluation, it is pretty good. Based on the formulation of the problem, the implementation process and the results of the Qafilah Da'wah Zulhijah STAI As-sunnah program are classified as good overall. However, they need improvement and adjustments in the future to make them more effective and efficient.